Construction superintendents : essential skills for the next generation - Holm, Len; Schaufelberger, John, 1942- (Abingdon, Oxon ; New York, NY : Routledge, 2019)
"Construction Superintendents: Essential Skills for the Next Generation is the first college level textbook designed to prepare you to take on a site supervisor role on a complex jobsite. The book covers the responsibilities of superintendents in relation to the jobsite project management team, the project owners, designers, and municipal services. The book outlines the development of the superintendent and his or her role and responsibilities in twenty-first century construction projects. Using examples and case studies of cutting-edge jobsite practices from the use of computer applications to leadership and capital development, this book lays out all the functions of a modern site superintendent in an easy-to-understand format"--
OCLC-licensed vendor bibliographic record.
Keywords: Building -- Superintendence -- Vocational guidance; ARCHITECTURE / Professional Practice; ARCHITECTURE / Project Management